Life and efficiency test of the tantalum lamp - Gilliford, William Thomas (My University, 1906)
Introduction: German manufacturers are producing a lamp for which they claim a longer life with greater efficiency than the ordinary carbon lamp possesses. Only a few of these have been introduced into this country and these chiefly for testing purposes. If these tantalum filament lamps are all that is claimed for them there would result a great saving. To compare the relative merits of these a carbon lamp, one new tantalum and a tantalum that had burned 300 hours are tested at stated intervals. The old tantalum was burned 1000 hours. The instruments used were as follows: Weston Direct Current Voltmeter. No. 13520 (0-150); Jewell Direct Current Ammeter No. 1476 (0-1.5) (0-15); Standard lamp No. 902 (16 candle power at 108.4 volts). The tests were all made on a Queen Standard Photometer fitted with a Lummer Brodhun screen. The scale extends the full length of the photometer bar, and is arranged to read in centimeters from each end and also when the standard is a 16 candle power lamp to read directly in candle power. The Lummer Brodhun screen was devised by two German electricians for use in the Reichsanstatt laboratory. The screen is of plaster of Paris, receiving light from either side. It is diffused upon mirrors on each side of the screen and from there it passes through two prisms to a lens where it is observed by the eye. One lamp will throw a circle in the center while around it with well defined edges the other lamp will throw its light. When the two shades are equal the spot will almost disappear and the relative intensity of the two lights will be inversely as the squares of their distances from the screen. The standard lamp used was No. 902 giving 16 candle power at 108.4 volts. It was burned no longer than was necessary so that the candle power of it would not fall. Almost ideal current was furnished for the lamp by the use of a storage battery of 60 cells. The voltage was adjusted by means of rheostats placed in series with the lamps. The accompanying curves show clearly the relation between the two lamps. For the new carbon lamp only the greatest candlepower in maximum position are plotted.
Citation: Gilliford, William Thomas. Life and efficiency test of the tantalum lamp. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Electrical Engineering; Tantalum Lamp; Lamps; Theses